Thought leaders : - Pandit, Shrinivas (Tata McGraw-Hill, 2001)
The book profiles 22 visionary managers of India, coming from diverse professions and backgrounds, and tries to provide an integrated view of what made these Indians so outstanding. The book summaries the sourse code of exceptional professional lives. Based on insightful interviews, it unveils the turning points in the lives of managers and leaders: the trigger points and events that lead to great journeys and success stories.